2005
DOI: 10.1095/biolreprod.104.031120
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin and Vascular Endothelial Growth Factor Are Cyclically Expressed in an Inverse Pattern During Bovine Ovarian Follicle Development1

Abstract: Angiogenesis does not normally occur in most adult tissues. However, in the ovary, there are cyclical vascular changes including angiogenesis that involve the interaction of numerous cytokines and growth factors. Angiogenic processes are regulated by a balance between pro- and antiangiogenic factors. The purpose of this study was to determine the expression of the antiangiogenic thrombospondin family and proangiogenic vascular endothelial growth factor (VEGF) in various sizes of healthy bovine follicles. Ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 50 publications
9
88
1
4
Order By: Relevance
“…Both VEGFA and FGF2 mediate their action through their high affinity tyrosine kinase receptors, namely VEGF receptor (VEGFR)-1 and VEGFR-2 and FGF receptor (FGFR)-1 and FGFR-2 respectively (Ferrara et al 2003, Wiedlocha & Sorenson 2004). In the pre-ovulatory follicle, granulosa cells are the major source of VEGFA, while FGF2 is mainly theca derived (Berisha et al 2000a, Greenaway et al 2005. Contrary to expectation, we have recently showed that FGF2 production, rather than VEGFA, is the dynamic driver during the follicle-luteal transition and early CL development in the cow (Robinson et al 2007).…”
Section: Introductioncontrasting
confidence: 58%
“…Both VEGFA and FGF2 mediate their action through their high affinity tyrosine kinase receptors, namely VEGF receptor (VEGFR)-1 and VEGFR-2 and FGF receptor (FGFR)-1 and FGFR-2 respectively (Ferrara et al 2003, Wiedlocha & Sorenson 2004). In the pre-ovulatory follicle, granulosa cells are the major source of VEGFA, while FGF2 is mainly theca derived (Berisha et al 2000a, Greenaway et al 2005. Contrary to expectation, we have recently showed that FGF2 production, rather than VEGFA, is the dynamic driver during the follicle-luteal transition and early CL development in the cow (Robinson et al 2007).…”
Section: Introductioncontrasting
confidence: 58%
“…Hayashi et al [36] reported several marker genes related to the largest follicle as the most viable follicle and the second largest follicles as a subordinate follicles in cows. In addition, several studies have reported genes related to healthy large developing follicles or subordinate follicles [31,34,35,37]. First, we compared the expression of marker genes between the two age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Of the apoptosis related genes, CCDC80, COL1A1, CTGF, DNAJB1, LGALS9, LTF, LNM, MT2A, MTH11, SOX4, and TIMP2 showed significant differences in expression levels between the two age groups (Supplementary Table 2). Table 3 lists the marker genes for the largest healthy follicles and the subordinate follicles in cows [31][32][33][34][35][36][37], and shows the expression levels of these genes in aged and young cows. All genes associated with subordinate follicles were expressed at lower levels in young cows.…”
Section: Comparison Of Gene Expression In Granulosa Cells Of Young Anmentioning
confidence: 99%
“…In the rat ovary, both TSP-1 and CD36 are localized primarily to the GC layer of antral follicles, while TSP-2 is expressed later during the ovulatory/early luteal phase (Petrik et al 2002). In the bovine, TSPs are co-expressed with CD36 on GC of follicles (Greenaway et al 2005). The specific functional role of CD36 in bovine preovulatory follicles remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%